Catalytic gold–platinum alloy nanoparticles and a novel glucose oxidase mimic with enhanced activity and selectivity constructed by molecular imprinting. Issue 36 (28th August 2019) - Lin, Fan; Yushen, Tian; Doudou, Lou; Haoan, Wu; Yan, Cui; Ning, Gu; Yu, Zhang
Abstract : Based on the research of the oxidase-like activity of various Au-based nanostructures, a novel AuPtNPs based GOD mimic with substrate-selectivity and an enhanced catalytic activity was constructed by molecular imprinting technology. Abstract : Gold nanoparticles have attracted a great deal of interest, but also exhibit inherent disadvantages of limited catalytic efficiency and lack of selectivity. Here Au–Pt alloy nanoparticles with significantly improved oxidase-like activity were synthesized, and on this basis, a novel mimic enzyme with substrate-selectivity and further enhanced catalytic efficiency was constructed. According to the exploration of the oxidase-like activities, Au–Pt alloy nanoparticles with a Au–Pt molar ratio of 1 : 1 were found to have the highest catalytic activity due to the combined effects of size and elemental composition. The Au–Pt alloy nanoparticles were coupled to magnetic microspheres to increase the stability and ease of magnetic separation. Besides that, glucose-bindable aminophenylboronic acid was employed to improve the affinity to the substrate and polymerized to build molecularly imprinted polymer shells with specific glucose binding pockets, which successfully led to about 200-fold higher catalytic efficiency ( k cat / K m ) than gold nanoparticles with an average diameter of 10 nm.